Arthropod community diversity and trophic structure: a comparison between extremes of plant stress - Trotter, R.T. III; Cobb, N.S; Whitham, T.G (Ecological entomology, 2008)
1. Previous studies have shown that plant stress and plant vigour impact the preference and performance of many insect species. Global climate-change scenarios suggest that some regions such as continental interiors may become increasingly subject to severe drought. In combination, these two issues suggest that drought-driven plant stress may impact insect communities on a landscape scale. While there have been many population studies relating plant stress to the life history of individual herbivore species, far less is known about how plant stress affects entire communities. 2. To study the effect of plant stress on arthropod communities, arthropods were sampled from the canopies of pinyon pines (Pinus edulis) growing at sites with a history of chronically high environmental stress (e.g. lower water potentials, soil moisture, and reduced growth rates), and those growing under more favourable conditions. Sampling in these environments yielded >59 000 arthropods, representing 287 species from 14 orders and 80 families, and revealed three major community patterns. 3. First, chronic stress significantly altered community composition. Second, trees growing under high stress supported about 1/10th the number of arthropods, and roughly half the species as trees growing under more favourable conditions. Third, of the 33 abundant herbivore species that exhibited a significantly skewed distribution towards either high- or low-stress trees, 73% were skewed with higher numbers on low-stress trees. 4. The pattern of potentially reduced arthropod diversity and abundance on stressed pines observed in this study may further compound the loss of species resulting from the recent, landscape-scale drought-induced mortality of pines in the southwestern USA.